YES Problem: f(a()) -> g(h(a())) h(g(x)) -> g(h(f(x))) k(x,h(x),a()) -> h(x) k(f(x),y,x) -> f(x) Proof: DP Processor: DPs: f#(a()) -> h#(a()) h#(g(x)) -> f#(x) h#(g(x)) -> h#(f(x)) TRS: f(a()) -> g(h(a())) h(g(x)) -> g(h(f(x))) k(x,h(x),a()) -> h(x) k(f(x),y,x) -> f(x) Matrix Interpretation Processor: dim=3 interpretation: [h#](x0) = [0 0 1]x0, [f#](x0) = [1 0 0]x0, [0 0 1] [0 0 1] [0 0 1] [1] [k](x0, x1, x2) = [1 1 1]x0 + [0 0 0]x1 + [1 1 1]x2 + [0] [0 0 0] [0 1 1] [1 0 0] [1], [0 0 0] [0] [g](x0) = [0 0 0]x0 + [1] [1 0 0] [1], [0 0 0] [h](x0) = [0 0 1]x0 [1 1 0] , [1 0 1] [0] [f](x0) = [0 0 0]x0 + [1] [1 0 0] [0], [1] [a] = [1] [0] orientation: f#(a()) = 1 >= 0 = h#(a()) h#(g(x)) = [1 0 0]x + [1] >= [1 0 0]x = f#(x) h#(g(x)) = [1 0 0]x + [1] >= [1 0 0]x = h#(f(x)) [1] [0] f(a()) = [1] >= [1] = g(h(a())) [1] [1] [0 0 0] [0] [0] h(g(x)) = [1 0 0]x + [1] >= [1] = g(h(f(x))) [0 0 0] [1] [1] [1 1 1] [1] [0 0 0] k(x,h(x),a()) = [1 1 1]x + [2] >= [0 0 1]x = h(x) [1 1 1] [2] [1 1 0] [1 0 1] [0 0 1] [1] [1 0 1] [0] k(f(x),y,x) = [3 1 2]x + [0 0 0]y + [1] >= [0 0 0]x + [1] = f(x) [1 0 0] [0 1 1] [1] [1 0 0] [0] problem: DPs: TRS: f(a()) -> g(h(a())) h(g(x)) -> g(h(f(x))) k(x,h(x),a()) -> h(x) k(f(x),y,x) -> f(x) Qed